1993
DOI: 10.1128/jb.175.13.4186-4196.1993
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a gene coding for a novel aspartate aminotransferase from Rhizobium meliloti

Abstract: Aspartate aminotransferase (AAT) is an important enzyme in aspartate catabolism and biosynthesis and, by converting tricarboxylic acid cycle intermediates to amino acids, AAT is also significant in linking carbon metabolism with nitrogen metabolism. To examine the role of AAT in symbiotic nitrogen fixation further, plasmids encoding three different aminotransferases from Rhizobium meliloti 104A14 were isolated by complementation of an Escherichia coli auxotroph that lacks three aminotransferases. pJA10 contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 68 publications
0
17
0
2
Order By: Relevance
“…However, within the group of aminotransferases many sequences are available, and similarity has been found for primary structures of tyrosine, histidinol-phosphate, and aspartate aminotransferases (33). For all of these enzymes, a few invariant residues that play an important role in structure and function of aminotransferases were found (1,33,60). However, enzymes belonging to the serine:pyruvate aminotransferase family, including SGAT from M. extorquens AM1, do not show any similarity with these enzymes in their primary structure, and most of the invariant residues were not found in corresponding locations of these sequences.…”
Section: Discussionmentioning
confidence: 99%
“…However, within the group of aminotransferases many sequences are available, and similarity has been found for primary structures of tyrosine, histidinol-phosphate, and aspartate aminotransferases (33). For all of these enzymes, a few invariant residues that play an important role in structure and function of aminotransferases were found (1,33,60). However, enzymes belonging to the serine:pyruvate aminotransferase family, including SGAT from M. extorquens AM1, do not show any similarity with these enzymes in their primary structure, and most of the invariant residues were not found in corresponding locations of these sequences.…”
Section: Discussionmentioning
confidence: 99%
“…However, our analysis and the most recent study (Graindorge et al, 2014) revealed that aminotransferases having PPA-AT activity are present not only in plants but also in a broader range of microbes. Plant PPA-ATs belong to the AspAT Ib class (Graindorge et al, 2010;Dal Cin et al, 2011;Maeda et al, 2011), which falls within subfamily Ig (Mehta et al, 1993;Jensen and Gu, 1996) and is distantly related to class-Ia AspATs (subfamily Ia) commonly present in all organisms (Alfano and Kahn, 1993;Okamoto et al, 1996;Nobe et al, 1998). In addition to plants, AspAT Ib-type enzymes having strong PPA-AT activity were found in Chlorobi bacteria (C. tepidum; Figure 3, Table 1) and Kinetic parameters were obtained for prephenate using aspartate amino donor (20 mM) in 10-min reactions using 0.5 and 2 mg/mL recombinant enzymes for wild type and mutants of Arabidopsis PPA-AT enzymes, respectively.…”
Section: Phylogenetic Distribution Of Ppa-at Enzymesmentioning
confidence: 99%
“…These findings were similar to AAT of Rhizobium meliloti (pH 8.0 -8.5). 12 At the same time, acidic or neutral ranges of optimum pH have been observed for AATs from Sulfolobus solfataricus (pH 5.8) and Bacillus YM-2 (pH 7.2). (Fig.…”
mentioning
confidence: 94%
“…12 We then determined the optimum pH and temperature for ApAAT with the transamination reaction toward L-aspartate and α-ketoglutarate. The optimum pH for ApAAT was 8.0 (Fig.…”
mentioning
confidence: 99%